Informação na gestão pública da saúde sob uma ótica antropológica: do global ao local no Estado de Minas Gerais, Brasil - Jose Wanderley Novato Silva (2008)
This study investigates the relationship between organizational culture of the local health departments in the state of Minas Gerais, Brazil - from the perspective of managers and employees - and how those agents deal with information on health from various sources. The organizational culture was seen as a way of shared work that includes attitudes constituent of an "informational conduct" and values and principles with specific meanings, forming an "informational culture". This culture was analyzed considering some of its external constraints - the local, regional, national and global cultures. The methodology included a quantitative analysis, done on a sample of municipalities of Minas Gerais, and a qualitative analysis, done in three municipalities intentionally chosen. The results showed various aspects related to how the secretaries treat the information in health - in line with aspects of the regional and national culture, which varies between modernity and backwardness. The studywas called "anthropological" because it was guided by concepts from this field of knowledge and tries to look with the "others eyes" at the reality of health information in the municipalities, then drawing local inferences - but its possible to compare and generalize the information by the triangulation of data obtained by the multireferences of the work. Thesymbolic level merited the construction of a specific hermeneutics, able to account for both the "location" of languages and signs as the many and complex disciplines involved in health - political, technical, social, cultural, economic, administrative sciences - especially since this area deals with complex concepts such as "health" and "illness", not comprehensible in a neutral manner, but instead, carrying multiple meanings socially conditioned.